Deteksi Migrasi Material Pembungkus Makanan ke Air karena Pemanasan - Girsang, Teguh Pribadi; Wijaya, I M. Mahaputra; Gunam, Ida Bagus Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
This research was aimed to detect if migration of additives or other components from plastic material used as packaging of hot food/drinks were occurred in warm-hot cooked temperature. In this works, plastic samples as like spoon, packaging, and wraps were taken directly from mainly street food vendors and shops. Pure water and plastics samples were mixed, and heat were introduced to induced migration. Three temperature of 60 °C, 80 °C, dan 100 °C, were each applied to induced migration for one hour. Migrations were detected using UV-Visible Spectroscopy, Fourier Transform InfraRed, and Gas Chromatography. Migrated polymer materials from plastics were detected through peaks of UV-visible absorption with water as background spectra were subtracted, and its functional groups were detected using FTIR spectroscopy. Gas chromatography was used to confirm if UV-visible and FTIR results were result from single component migration. Keywords: polymer, migration, temperature, plastics, wavelength.